Critical Minerals - Vital Ingredients and Huge Challenge to Energy Transition - SARMIZA PENCEA (Global Economic Observer)
As mankind engages on yet another bold development cycle, all the newly-designed high technologies for a more sustainable future, primarily the technologies required by the energy transition, depend, inevitably, in terms of their implementation, on the mineral resources that our planet can provide. Especially the minerals deemed critical. This article looks at the impact that the switch to a new paradigm in the way we produce and consume energy is inflicting on the global demand for critical minerals, at the challenges and risks posed by this unavoidable process, as well as at the opportunities and the positive spillovers brought by it, providing relevant examples and data from the industries involved. Throughout this analysis, the conventional fossil fuels-based energy system and the renewable energy-based new system are compared from different angles, both in terms of their impact on the industries and markets of critical minerals, and of their strong influence on the socioeconomic environment, on the international relations between states and the strategic and geopolitical interplay between the most important global technological powers of our time.